Implementasi Model Problem Based Learning Berbantuan Google Sites untuk Meningkatkan Kemampuan Pemahaman Konsep Peserta Didik pada Materi Fungsi Kuadrat - Sih Mustika, Gandes; Astuti, Dwi; Aprilia, Anna; Yuliandari, Yuliandari (Jurnal Inovasi Pembelajaran Matematika, 2024)
Most students experience difficulties in understanding mathematical concepts presented by the teacher. This research aims to improve students' conceptual understanding of quadratic functions by implementing a problem-based learning (PBL) model aided by Google Sites. This classroom action research adopts the Kemmis and McTaggart model. The study was conducted in two cycles, with two meetings in each cycle, and the subjects were 36 students of class X-6 at SMA Negeri 1 Sewon. The data collection instruments were learning implementation observation sheets and conceptual understanding test questions. A quantitative descriptive data analysis technique was used with a success criterion of more than 70% of students having a conceptual understanding at least in the high category based on test results. The results showed that the application of the PBL model aided by Google Sites could improve the conceptual understanding abilities of class X-6 students at SMA Negeri 1 Sewon. The greatest improvement in students' mathematical conceptual understanding of quadratic functions between pre-action and cycle I was on the indicator of restating the concept, which was 65.97%. The greatest improvement in students' mathematical conceptual understanding of quadratic functions between cycle I and cycle II was in presenting concepts in various mathematical representation forms, which was 40.28%. In general, the achievement in cycle II was 83.33% of students having a high conceptual understanding ability. This indicates that the student's conceptual understanding in cycle II met the success criteria, which is more than 70% of students having a high conceptual understanding ability.